New entanglement-assisted MDS quantum codes from constacyclic codes - Koroglu, Mehmet E. (SPRINGER, 2019)
Construction of good quantum codes via classical codes is an important task for quantum information and quantum computing. In this work, by virtue of a decomposition of the defining set of constacyclic codes we have constructed eight new classes of entanglement-assisted quantum maximum-distance-separable codes.
Keywords: Entanglement-assisted quantum error-correcting codes; Constacyclic codes; MDS codes; ERROR-CORRECTING CODES; Physics